The Varying Interpretations of Public Interest: Making Sense of Finnish Urban Planners’ Conceptions - Sari Puustinen; Raine Mäntysalo; Karoliina Jarenko (Scientific Research Publishing, 2022)
During the past decades, the concept of public interest has been severely criticized. It nevertheless remains to be a key normative reference point against which public planning may be evaluated and justified. The article claims that there are multiple conceptions of public interest that coexist in everyday planning practice. These conceptions are grounded in the age-old debate on the duties of the State. In the article, four different approaches to public interest were recognized on the basis of two dimensions of the concept. These dimensions are individual/collective and regulation/non-regulation. The theoretical assumptions were tested with interview data of Finnish planning professionals. The coexistence of multiple conceptions of public interest was revealed. This ambiguity makes public interest dubious as a rhetorical tool. Without the explication of the discursive context, the concept is largely devoid of meaning. Thus, when truly seeking justification to planning decisions, with reference to “public interest”, the explication of the context and the discursive framework applied is necessary.